2009
DOI: 10.4028/www.scientific.net/ssp.147-149.530
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Engine Health/Maintenance Status Monitoring with Use of Phase-Discrete Method of Blade Vibration Monitoring

Abstract: The intended aim of the paper was to present a short review of more than 15 years of experience of ITWL in the field of applying the signal of actual rotational speed (aperiodic and oscillation components thereof) to the expert diagnosing of aero-engines, including identification of low- and high-cycle fatigue (LCF, HCF) of critical structural members. What has been presented is some essential metrological bearings of the non-contact technique of measuring the engine’s rpm with some flexible key phasors (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…However the method can be used in a monitoring system to track changes of vibration frequency. It is confirmed that the fundamental frequency decreases when a fatigue crack is initiated and developed [11], [13], [17]. …”
Section: Single Blade Spectrumsupporting
confidence: 53%
See 3 more Smart Citations
“…However the method can be used in a monitoring system to track changes of vibration frequency. It is confirmed that the fundamental frequency decreases when a fatigue crack is initiated and developed [11], [13], [17]. …”
Section: Single Blade Spectrumsupporting
confidence: 53%
“…The following sections discuss analysis methods of TOA signal we use in single or dual sensor systems. Many of presented concepts were implemented in the software of SPL-1b system in mid 1990s' [11], [17].…”
Section: Fig 6 Example Of Stack Pattern For a Single Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…They were successfully employed in monitoring system for blade vibration, which was developed in Poland for turbojet training aircrafts (Szczepanik & Witoś, 1998;Witoś & Szczepanik, 2005). It is the first airborne tip-timing system implemented worldwide and is still in use by Polish Air Forces.…”
Section: Parameters Of Signals Received From Inductive Sensorsmentioning
confidence: 99%